Analisa Perbandingan Laporan Keuangan Tahun 2019-2023 Terhadap Kinerja Perusahaan PT XYZ”. - Bachtiar, Muchlis; Rangkuti, Zulkifli; Purnomo, Hadi (Ekonomi & Bisnis, 2025)
This study aims to analyse the financial performance of food and beverage companies in Cirebon from 2019 to 2023 using financial statements. This research uses descriptive and comparative analysis methods to evaluate the changes and trends that occurred in the company's financial performance during the five-year period. Financial data obtained from the annual reports of food and beverage companies in Cirebon were used to identify the main factors affecting profitability, liquidity, activity and solvency. The results of the analysis showed significant changes in the financial performance of food and beverage companies in Cirebon during the study period, with increases or decreases occurring in various financial indicators. Factors such as macroeconomic conditions, management strategies, and industry factors particularly in the sector of food and beverage companies play an important role in financial results. This study provides an in-depth insight into the dynamics of financial performance of food and beverage companies in Cirebon over the past five years and its implications for future management strategies. The findings are expected to provide valuable guidance for stakeholders, including company management and investors, in making better decisions and in planning future strategies to achieve long-term growth and sustainability. Keyword : financial statements, ratio, company performance